Technical and economic viability and nutritional quality of mombasa guinea grass silage production - Galindo, Fernando Shintate [UNESP]; Beloni, Tatiane; Buzetti, Salatiér [UNESP]; Teixeira, Marcelo Carvalho Minhoto [UNESP]; Dupas, Elisângela [UNESP]; Ludkiewicz, Mariana Gaioto Ziolkowski [UNESP] (Editora da Universidade Estadual de Maringá - EDUEM, 2018)
The objective of this study was to evaluate the viability of pasture with high production capacity and the potential for production of silage using different sources and doses of nitrogen (N) by quantifying the productivity of dry matter (DM), some qualitative characteristics, the total cost of production (TC) and total operating cost (TOC) of silage production. The experimental design was randomized block in a factorial scheme with four replications including two sources of nitrogen (urea and ammonium nitrate) and five N doses (0, 50, 100, 150, and 200 kg ha-1 by cutting). The increase in N provided greater DM and crude protein content and reduced the fiber content in neutral detergent. The source of N did not affect the chemical composition, and therefore, it is recommended to use urea due to the ease of acquisition and higher economic return. The production of Mombasa silage can be economically viable due to high DM and crude protein content combined with low production costs. The smallest TC and TOC were obtained in the absence of nitrogen fertilization; however, the proper management of N ensures high productivity in cattle feed with higher total profit when using 100 kg ha-1 N by cutting with ammonium nitrate.

Objetivou-se estudar a viabilidade de uma pastagem com alta capacidade produtiva e o potencial para produção de silagem de capim, utilizando fontes e doses de nitrogênio (N), quantificando-se a produtividade de matéria seca (PMS), algumas características bromatológicas, o custo total de produção (CT) e o custo operacional total (COT) da produção de silagem. O delineamento experimental foi em blocos casualizados, adotando um esquema fatorial com quatro repetições, sendo duas fontes de nitrogênio: ureia, e nitrato de amônio, e cinco doses de N (0, 50, 100, 150 e 200 kg ha-1 por corte). O incremento de N propiciou maior PMS e teor de proteína bruta, além de diminuir os teores de fibra em detergente neutro. As fontes de N, não influenciaram na composição química, e desta forma recomenda-se utilizar a ureia em função da facilidade de aquisição e maior retorno econômico. A produção de silagem de capim-Mombaça pode ser economicamente viável em função da elevada PMS e proteína bruta, aliado ao baixo custo de produção. O menor CT e COT foi obtido na ausência da adubação nitrogenada, entretanto, o manejo adequado de N garante boa produtividade e rendimento na alimentação do rebanho, com maior lucro total obtido na utilização de 100 kg ha-1 de N por corte com a fonte nitrato de amônio.
Viabilidade técnica, econômica e qualidade nutricional da produção de silagem de capim-mombaça
Keywords: nitrogen fertilization; chemical analysis; production cost; tropical grass; Panicum maximum; adubação nitrogenada; análises bromatológicas; custo de produção; gramínea tropical; Panicum maximum